Exercise training-attenuated insulin resistance and liver injury in elderly pre-diabetic patients correlates with NLRP3 inflammasome - Zhang, Tan; Tian, Jingjing; Fan, Jingcheng; Liu, Xiangyun; Wang, Ru (Frontiers in Immunology, 2023)
Background: Diabetes is one of the most common metabolic diseases and continues to be a leading cause of death worldwide. The NLRP3 inflammasome has been shown to exert detrimental effects on diabetic models. However, evidence linking NLRP3 inflammasome and pre-diabetes has been scarcely explored. Herein, we aimed to determine whether the NLRP3 inflammasome correlates with insulin resistance and liver pathology in a cohort of pre-diabetic subjects. Methods: 50 pre-diabetic subjects were randomly assigned to a Pre-diabetes Control (DC, n=25) and a Pre-diabetes exercise (DEx, n=25) group. 25 Normal subjects (NC) were selected as controls. The DEx group performed a 6-month combined Yijingjing and resistance training intervention, while DC and NC group remained daily routines. Clinical metabolic parameters were determined with an automatic biochemistry analyzer; inflammatory cytokines were quantified by the ELISA assay; the protein expressions of NLRP3 inflammasome components in PBMCs were evaluated by Western Blot. Results: The insulin resistance, liver injury and NLRP3 inflammasome activity were higher in pre-diabetic individuals than in normal control group. However, 6-month exercise intervention counteracted this trend, significantly improved insulin sensitivity, reduced liver injury and inhibited the overactivation of NLRP3 inflammasome in pre-diabetic subjects. Moreover, positive correlations between insulin resistance, liver pathology and NLRP3 inflammasome were also found. Conclusions: Our study suggests that exercise training is an effective strategy to alleviate insulin resistance and liver injury in elderly pre-diabetic subjects which is probably associated with the inhibition of NLRP3 inflammasome activity.